2020
DOI: 10.1101/2020.05.26.111856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gsta4 controls apoptosis of differentiating adult oligodendrocytes during homeostasis and remyelination via the mitochondria-associated Fas/Casp8/Bid-axis

Abstract: Arrest of oligodendrocyte (OL) differentiation and remyelination following myelin damage in Multiple Sclerosis (MS) are associated with disease progression but the underlying mechanism are elusive. We show that Glutathione S-transferase 4α (Gsta4) is highly expressed during adult OL differentiation and that its loss prevents differentiation into myelinating OLs. Also, Gsta4 appeared to be a novel target for Clemastine, in clinical trial for MS. Over-expression of Gsta4 reduced the expression of Fas and activit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“… S. aureus has become one of the major causes involved in a wide range of community- or hospital-acquired infections. Chronic or persistent S. aureus infection has posed a serious threat to human health due to recalcitrant biofilms formation which is highly tolerant of traditional antibiotics ( 24 , 25 ). Clemastine is one of the first-generation antihistamines with slight side effects, such as drowsiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… S. aureus has become one of the major causes involved in a wide range of community- or hospital-acquired infections. Chronic or persistent S. aureus infection has posed a serious threat to human health due to recalcitrant biofilms formation which is highly tolerant of traditional antibiotics ( 24 , 25 ). Clemastine is one of the first-generation antihistamines with slight side effects, such as drowsiness.…”
Section: Discussionmentioning
confidence: 99%
“…Clemastine is one of the first-generation antihistamines with slight side effects, such as drowsiness. Recent studies found clemastine might be used as the remyelinating therapy of multiple sclerosis and seldom reports have demonstrated the inhibition of clemastine on the multiple growth stages of plasmodium parasite and mycobacterial growth ( 25 27 ). These studies strongly suggest the complicated physiological function of clemastine against a variety of human diseases, while data from studies addressing clemastine for the chemotherapy of S. aureus infection are still lacking.…”
Section: Discussionmentioning
confidence: 99%